If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Rx + h = sx + -1k Reorder the terms: h + xR = sx + -1k Reorder the terms: h + xR = -1k + sx Solving h + xR = -1k + sx Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1xR' to each side of the equation. h + xR + -1xR = -1k + sx + -1xR Combine like terms: xR + -1xR = 0 h + 0 = -1k + sx + -1xR h = -1k + sx + -1xR Simplifying h = -1k + sx + -1xR
| 5(2x-6)=150 | | 1.75(5*3.25)= | | 5n+3=6 | | 2n-9=14n+1 | | (2x-3)(x-1)-(1-x)(1+x)=-4(x+1)(x-1) | | 0=14x^2-46x+12 | | (-2h+1)+2(3h-4)= | | 2n-9-14n=1 | | 3*3-2(-2)-3*-2= | | -x+6=31 | | 2(x)-4=48 | | 3(-x)+2=2(-x)+8 | | 4x-32=5x-56 | | 12*.33+6=10 | | 7x+1=2x+5 | | y=16*1.5x | | 3-5k+19=17 | | y-20=55(x-2) | | 6x=-810 | | -4x+2-3x=-6-7x+5 | | 2x(-y)= | | .33*2= | | -6(-16)= | | 6(x+3)=-2(-9+5x) | | 2x^2=-11x-12 | | -x+8-2x+5x-3=-15 | | 6(x+3)=-2(-5+5x) | | (2m+5)-(3-6m)= | | -6(n+1)= | | (x^2)2=3x | | 8+x+2x=-1 | | 12k^2-36k+27=0 |